We're looking for a solution of the form
![y=\displaystyle\sum_(n=0)^\infty a_nx^n=a_0+a_1x+a_2x^2+\cdots](https://img.qammunity.org/2020/formulas/mathematics/college/zozwp8b5qye5dchkg1fpkv7n90aypusi96.png)
Given that
, we would end up with
.
Its first derivative is
![y'=\displaystyle\sum_(n=0)^\infty na_nx^(n-1)=\sum_(n=1)^\infty na_nx^(n-1)=\sum_(n=0)^\infty(n+1)a_(n+1)x^n](https://img.qammunity.org/2020/formulas/mathematics/college/55pa29nebw7jd827tm7jnrk2npy7p3p5bm.png)
The shifting of the index here is useful in the next step. Substituting these series into the ODE gives
![\displaystyle\sum_(n=0)^\infty(n+1)a_(n+1)x^n-\sum_(n=0)^\infty a_nx^n=x](https://img.qammunity.org/2020/formulas/mathematics/college/ltczt4yipmfzod2yb58gq2o6w6m6rtjbh5.png)
Both series start with the same-degree term
, so we can condense the left side into one series.
![\displaystyle\sum_(n=0)^\infty\bigg((n+1)a_(n+1)-a_n\bigg)x^n=x](https://img.qammunity.org/2020/formulas/mathematics/college/7f93te67giv81k2tsiyxp9yd9koy2j5uba.png)
Pull out the first two terms (
and
) of the series:
![a_1-a_0+(2a_2-a_1)x+\displaystyle\sum_(n=2)^\infty\bigg((n+1)a_(n+1)-a_n\bigg)x^n=x](https://img.qammunity.org/2020/formulas/mathematics/college/df1pea0m4t6nj2vre10lqe7kon6v4ffnp3.png)
Matching the coefficients of the
and
terms on either side tells us that
![\begin{cases}a_1-a_0=0\\2a_2-a_1=1\end{cases}](https://img.qammunity.org/2020/formulas/mathematics/college/loy209j7hc9r45iqxayvs83aeaujc96jnf.png)
We know that
, so
and
. The rest of the coefficients, for
, are given according to the recurrence,
![(n+1)a_(n+1)-a_n=0\implies a_(n+1)=(a_n)/(n+1)](https://img.qammunity.org/2020/formulas/mathematics/college/1x4g33ksqvs3gssgh5thpo1f5cs6iw5b0c.png)
so that
,
, and
. So the 5th degree approximation to the solution to this ODE centered at
is
![y\approx1+x+x^2+\frac{x^3}3+(x^4)/(12)+(x^5)/(60)](https://img.qammunity.org/2020/formulas/mathematics/college/eqikh5p0mnj2y9n5fkhpmxpn7uw627gtnb.png)